2007
DOI: 10.1007/s00277-007-0361-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cross-resistance to nucleoside analogues and inhibitors of topoisomerase 1 and 2 in acute myeloid leukemia

Abstract: Only about one third of all patients with acute myeloid leukemia (AML) will be cured by common chemotherapy regimens. Susceptibility towards chemotherapy either of the leukemic bulk or the leukemic stem cell is considered the major determining parameter for long-term outcome. The purpose of the present study was to investigate whether chemoresistance was correlated between different antileukemic drugs or not. We determined the lethal concentration of chemotherapy necessary to reduce viability of cells to 50% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Almost all published reports on cross‐resistance recorded a P ‐value alongside the r ‐values (Kivekas et al , 2002; Lofgren et al , 2005; Styczynski et al , 2005; Hubeek et al , 2006; Fiegl et al , 2008; Lindhagen et al , 2008). Unfortunately, statistical tests of correlation are designed to determine the strength of a correlation – in this case, the likelihood that two drugs have the same or similar action (the null hypothesis being no correlation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all published reports on cross‐resistance recorded a P ‐value alongside the r ‐values (Kivekas et al , 2002; Lofgren et al , 2005; Styczynski et al , 2005; Hubeek et al , 2006; Fiegl et al , 2008; Lindhagen et al , 2008). Unfortunately, statistical tests of correlation are designed to determine the strength of a correlation – in this case, the likelihood that two drugs have the same or similar action (the null hypothesis being no correlation).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in CLL it is generally agreed that fludarabine and cladribine are cross-resistant, as patients resistant 'in vivo' to the former had a poor response rate to the latter (Juliusson et al, 1992;O'Brien et al, 1994). Laboratory studies show similar results with the advantage that ex vivo experiments can be performed simultaneously as opposed to having to be sequential in the patient (Fiegl et al, 2008). Cross-resistance in vitro, however, has generally been performed on relatively small numbers of patients (Lindhagen et al, 2008) giving potentially dubious results.…”
mentioning
confidence: 99%
“…Some previous studies reported that patient samples with a high ex vivo drug resistance towards Ara C were not only resistant towards other deoxynucleotide analogues (e.g., fludarabine or gemcitabine) [18], but also towards other chemotherapeutics with different modes of action (such as VP16 or DNR) [19,20]. An intrinsic property of leukemic cells that is thought to play an important role in resistance to Ara C, is the ability to transport the drug across the plasma membrane in both directions [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of problems have been raised by the evasion of leukemia cells from anti‐cancer drugs and acquisition of resistance in leukemia cure . A serious matter is that surviving cells from first‐line chemotherapy evolve into more malignant cancer cells that become less sensitive to re‐induction regimens . Therefore, discovering a novel class of medicine with a different killing mechanism from those of established drugs is required.…”
Section: Introductionmentioning
confidence: 99%